2012
DOI: 10.1158/1078-0432.ccr-12-0738
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Targeted and Cytotoxic Agents in Murine Subcutaneous Tumor Models Correlates with Clinical Response

Abstract: Purpose: Immunodeficient mice transplanted with subcutaneous tumors (xenograft or allograft) are widely used as a model of preclinical activity for the discovery and development of anticancer drug candidates. Despite their widespread use, there is a widely held view that these models provide minimal predictive value for discerning clinically active versus inactive agents. To improve the predictive nature of these models, we have carried out a retrospective population pharmacokinetic-pharmacodynamic (PK-PD) ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
123
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 33 publications
(42 reference statements)
0
123
0
Order By: Relevance
“…2, blue bars). BHPI easily exceeded the goal of >60% tumor growth inhibition proposed as a benchmark more likely to lead to clinical response (20). Furthermore, BHPI, at 10 mg/kg every other day, ultimately stopped tumor growth and final tumor weight was reduced ∼60% compared with controls (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2, blue bars). BHPI easily exceeded the goal of >60% tumor growth inhibition proposed as a benchmark more likely to lead to clinical response (20). Furthermore, BHPI, at 10 mg/kg every other day, ultimately stopped tumor growth and final tumor weight was reduced ∼60% compared with controls (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that preclinical efficacy in xenografts may predict the clinical efficacy. 23,24 Therefore, understanding the exposureresponse relationship for drug candidates in a preclinical model could aid in predicting the optimal dose and regimen in patients. 25 For example, the active plasma concentration of cetuximab in a mouse xenograft model was fairly comparable with those observed in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor xenografted mice serve as a "workhorse" efficacy model to assess antitumor effects of novel agents and thus are widely used in oncology drug discovery (Johnson et al, 2001;Kelland, 2004;Peterson and Houghton, 2004;Wong et al, 2012b). Our previous investigation showed that a correlation exists between antitumor activity in xenografted/allografted mice and clinical response, provided that two conditions were fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation showed that a correlation exists between antitumor activity in xenografted/allografted mice and clinical response, provided that two conditions were fulfilled. These conditions were 1) that species differences in mouse and human PK had to be normalized, and 2) that the specific xenograft model used in the assessment had to be relevant to human disease being treated (Wong et al, 2012b). At the time of our work with GDC-0917, we arbitrarily set ED 50 and ED 90 as two efficacy end points from which we would evaluate the compound in a breast cancer model.…”
Section: Discussionmentioning
confidence: 99%